Evaluation of a short-term ingestion of zearalenone, fumonisin, and aflatoxin mixture incorporated, at low concentration, into the diet of weanling piglets and the effect of an anti-mycotoxin feed additive - Antonio Diego Brandão Melo (Semina: Ciências Agrárias, 2018)
An experiment was conducted to evaluate the toxic effects of short-term ingestion of a zearalenone, fumonisin, and aflatoxin mixture, at low concentration, into the diet of weanling piglets and to assess the protective efficacy of an anti-mycotoxin feed additive. For 21 days, piglets were exposed to control or multi-mycotoxin treatment with or without the anti-mycotoxin additive. Growth performance was measured after 21d. Blood samples were taken to serum biochemical analysis and for quantify levels of circulating mononuclear immune cells. Effects on organs weights and histological changes, and expression levels of COX-2 and TNF-α in the liver and jejunum were evaluated. Overall, the multimycotoxin treatment had no effect on measured variables, and no adverse histopathological changes in organs were observed. The total serum protein concentration was higher in animals that received the multi-mycotoxin treatment; however, levels remained within normal limits for weanling piglets. In conclusion, the short-term multi-mycotoxin mixture, at the dose levels evaluated in this study, seems not affect the health of weanling piglets through the evaluated parameters. The absence of toxicity associated with the multi-mycotoxin treatment rendered it impossible to evaluate the efficacy of the anti-mycotoxin additive.